Defense Strategy Against MSME Performance - Putri, Eskasari; Bandi (Riset Akuntansi dan Keuangan Indonesia, 2023)
The Covid-19 pandemic has hurt various sectors, one of which is MSMEs. During the pandemic, MSMEs experienced a decrease in sales or turnover, and a few experienced an increase. This quantitative research aims to analyze survival strategies (financial attitudes, marketing strategies, locus of control, and self-efficacy) on the performance of MSMEs with business resilience as a moderating variable. This study involved 60 respondents (SME actors) in Surakarta who were positioned as research subjects. The data used are primary, data collection using survey methods with interview techniques using questionnaires. The collected data were analyzed using SPSS software by performing instrument tests, classical assumption tests, hypothesis testing, and Moderated Regression Analysis (MRA) tests. The results of this study inform that, 1) financial attitudes have no effect on the performance of MSMEs, 2) marketing strategies do not affect the performance of MSMEs, 3) Locus of control affects the performance of MSMEs, 4) Self-efficacy affects the performance of MSMEs, 5) Financial attitude does not affect MSME resilience, 6) Marketing strategy does not affect MSME resilience, 7) Locus of control affects MSME resilience, 8) Self-efficacy affects MSME resilience, 9) Business resilience does not affect MSME performance, 10 ) Business resilience does not strengthen the relationship between financial attitudes and MSME performance, 11) Business resilience does not strengthen the relationship between marketing strategy and MSME performance, 12) Business resilience does not strengthen the locus of control relationship on MSME performance, 13) Resilience does not strengthen the relationship between self-efficacy and MSME performance. . Following up on the findings in this study, survival strategies on business performance must be optimized, one of which is through marketing strategies, financial attitudes and paying attention to the importance of self-confidence (locus of control & control).